Octreotide combined with pantoprazole in the treatment of elderly patients with peptic ulcer complicated by upper gastrointestinal bleeding - Yang, Ming; Zhang, Shu-Qin; Huang, Jing (Frontiers in Pharmacology, 2025)
BackgroundUpper gastrointestinal bleeding (UGIB) is a serious complication of peptic ulcer (PU), particularly in elderly patients who are at higher risk for adverse outcomes. While pantoprazole is widely used for acid suppression, adding octreotide may enhance hemostatic efficacy by reducing splanchnic blood flow. This study evaluates the efficacy of octreotide combined with pantoprazole in managing UGIB in elderly PU patients.MethodsA retrospective evaluation was conducted from January 2021 to December 2023, including 116 elderly patients (≥60 years) diagnosed with PU and UGIB. Patients were divided into two groups: the control group (n = 60), receiving pantoprazole, and the observation group (n = 56), receiving a combination of octreotide and pantoprazole. Both groups received standard supportive care. Key clinical indicators assessed included hemostasis time, gastric pH, hemoglobin levels, and coagulation parameters, such as prothrombin time (PT), thrombin time (TT), and fibrinogen (Fib) levels. Statistical analysis was performed using SPSS software (Version 27.0), with a significance threshold of p < 0.05.ResultsThe observation group exhibited a significantly higher effective hemostasis rate (91.07%) compared to the control group (73.33%, p = 0.013). Hemostasis time was shorter in the observation group (27.35 ± 3.52 h) than in the control group (33.04 ± 4.45 h, p < 0.001). Post-treatment gastric pH was significantly higher in the observation group (6.74 ± 1.38) compared to the control group (5.29 ± 1.20, p < 0.001), contributing to improved ulcer healing. Hemoglobin levels and coagulation function (PT, TT, and Fib levels) also showed greater improvement in the observation group, suggesting enhanced recovery and hemostatic stability.ConclusionThe combination of octreotide and pantoprazole is associated with improved hemostatic efficacy in elderly patients with peptic ulcers and upper gastrointestinal bleeding. It is linked to reduced hemostasis time, optimized gastric pH, and improved coagulation function. These findings suggest its potential as a promising approach for managing UGIB in this population.